2017
DOI: 10.1371/journal.pone.0188750
|View full text |Cite
|
Sign up to set email alerts
|

GnRH receptor gene mutations in adolescents and young adults presenting with signs of partial gonadotropin deficiency

Abstract: Biallelic, partial loss-of-function mutations in GNRHR cause a wide spectrum of reproductive phenotypes from constitutional delay of growth and puberty to complete congenital hypogonadotropic hypogonadism. We studied the frequency of GNRHR, FGFR1, TAC3, and TACR3 mutations in nine adolescent and young adult females with clinical cues consistent with partial gonadotropin deficiency (stalled puberty, unexplained secondary amenorrhea), and describe phenotypic features and molecular genetic findings of monozygotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
4
12
0
2
Order By: Relevance
“…In the present study, the AltEnd event in ESRRA more exclusively occurred in pre-puberty, compared with post-puberty in ovary. It has been reported that TACR3 directly regulates the release of GnRH and the onset of puberty (Hietamaki et al, 2017). In the present study, we found that Cassette of TAC3R was more specifically identified in post-puberty in pituitary, compared with that of pre-puberty.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, the AltEnd event in ESRRA more exclusively occurred in pre-puberty, compared with post-puberty in ovary. It has been reported that TACR3 directly regulates the release of GnRH and the onset of puberty (Hietamaki et al, 2017). In the present study, we found that Cassette of TAC3R was more specifically identified in post-puberty in pituitary, compared with that of pre-puberty.…”
Section: Discussionsupporting
confidence: 58%
“…Further, analysis of sex ratio for CHH in families with autosomal inheritance demonstrates that the sex ratio is close to being equal (194,195). Importantly, partial congenital hypogonadotropic hypogonadism may still be underdiagnosed due to subtle clinical presentation that resembles functional hypothalamic amenorrhea (131,196). Several reasons could help to explain the underdiagnosis of CHH females:…”
Section: Bias Regarding the Reduced Prevalence Of Chh In Femalesmentioning
confidence: 99%
“… 8 9 Mutations in gonadotropin-releasing hormone receptor gene ( GNRHR ), fibroblast growth factor receptor 1 gene ( FGFR1 ), tachykinin 3 ( TAC3 ), and tachykinin receptor 3 gene ( TACR3 ) cause PCHH. 10 Because of lack of clear diagnostic criteria, previous studies of PCHH were mainly limited to description of symptoms and characterization of mutant genes. There have been no reports on gonadotropin treatment for a Chinese population with PCHH.…”
Section: Introductionmentioning
confidence: 99%